Role of Shirodhara in the Management of Depression (International Journal of Ayurveda and Pharma Research, 2023)
Depression is a state of low mood and aversion to activity that can affect a person's thoughts, behaviour, tendencies, feelings, and sense of well-being. It is also a symptom of some physical diseases and a side effect of some drugs and medical treatments. It is one of the most common mental disorder affecting a large number of people worldwide. It can be caused due to various factors including unfavourable environmental conditions, psychological conditions, biological causes or some genetic cause. Overwhelming sadness or isolation, headaches or migraine, anxiety over everyday activities, moodiness, irritability and agitation, chronic fatigue, low self-esteem are main symptoms of depression. On reviewing the symptoms of depression, we can say that according to Ayurveda there are two conditions which can be correlated to Depression- namely- Vishada and Avsada. Sometimes it has also been correlated to Kaphaj Unmada. Modern medicine use antidepressants which on long term use have serious side effects. On the other hand, Ayurveda follows a multidimensional approach with the use of proper diet, lifestyle, Yoga, Rasayana therapy along with classical medications. Panchakarma therapies especially Shirodhara play an important role in enhancing the patient’s condition with depression. Shirodhara is a Panchakarma therapy that is quite popular nowadays, and this review article has focused on how it can be used to treat mental illnesses like depression. In numerous investigations, Shirodhara was found effective on subjective as well objective criteria.